Characterisation of new full-length HIV-1 subtype D viruses from South Africa - Loxton, Andre Gareth; Janse van Rensburg, E.; Engelbrecht, S. (2010)
Thesis (MSc (Medical Virology )--University of Stellenbosch, 2004.